Does the sequence of addition of herbicide and adjuvants to the spray solution influence sicklepod control? - Tavares Ramos, Maria Fernanda [UNESP] (2019)
The use of adjuvants associated with herbicides aims at improving the performance of application and the consequent increase in the biological effect of the treatment. However, the sequence of product added to the sprayer tank can influence the phytosanitary spray solution. Thus, this study aimed to evaluate the control of Senna obtusifolia as a function of the sequence of addition of the herbicide aminopyralid + fluroxypyr and adjuvants in the preparation of spray solution. Two herbicide doses (1 and 2 L c.p. ha-1) associated with the adjuvants mineral oil (MO), silicone polyether copolymer (SIL), and a mixture of phosphatidylcholine and propionic acid (LEC), all in the proportion of 0.3% v v-1, with alternate addition to the spray solution to evaluate the effects of the preparation sequence. The spray solution volume considered was 150 L ha-1. Evaluations of spray solution stability were performed from the visual evaluation of homogeneity, electrical conductivity, and pH. The effect of treatment on S. obtusifolia control was measured using a scoring scale and dry matter. Correlation coefficients between the evaluations were also determined. No difference of the preparation sequence of spray solution was observed for stability, pH, and electrical conductivity, but an influence was observed on S. obtusifolia control, without changing dry matter accumulation. The treatment with the adjuvant LEC previously added to the herbicide provided a higher control rate at the highest dose, while the adjuvant SIL had the opposite effect.